2012
DOI: 10.1038/npp.2012.197
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted-In-Schizophrenia-1 Gln31Leu Polymorphism Results in Social Anhedonia Associated with Monoaminergic Imbalance and Reduction of CREB and β-arrestin-1,2 in the Nucleus Accumbens in a Mouse Model of Depression

Abstract: Disrupted-in-schizophrenia-1 (DISC1) is associated with mental disorders, including major depression. We previously showed that DISC1-Q31L mutant mice have depression-like behaviors and can therefore be used to study neurobiological mechanisms of depression and antidepressant (AD) medication action. First, we found reduced levels of dopamine, serotonin and norepinephrine in the nucleus accumbens (NAC) of DISC1-Q31L mutants. Next, we assessed social-conditioned place preference as a reward-dependent task and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 77 publications
(112 reference statements)
3
48
1
Order By: Relevance
“…Previous studies have shown that CREB and c‐fos are downstream proteins of the ERK signalling pathway . Cyclic adenosine monophosphate response element‐binding has been shown to be associated with learning and memory . Consistent with previous reports, the results of the present study indicated that OXT reduced ERK phosphorylation and downregulated the expression of CREB and c‐fos.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that CREB and c‐fos are downstream proteins of the ERK signalling pathway . Cyclic adenosine monophosphate response element‐binding has been shown to be associated with learning and memory . Consistent with previous reports, the results of the present study indicated that OXT reduced ERK phosphorylation and downregulated the expression of CREB and c‐fos.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, deficits in social interaction, working memory, and executive function have been reported in some DISC1 mutant strains . Several strains of DISC1 mutant mice also demonstrate altered dopamine function in the striatum, with increased levels of dopamine D2 receptors and dopamine transporter, and decreased basal levels of dopamine . These studies indicate DISC1 mice to be a useful animal model for investigating schizophrenia‐associated symptoms, and suggest DISC1 as a potential therapeutic target for psychiatric conditions, including schizophrenia …”
Section: The Role Of the Basal Ganglia In Psychiatric Disordersmentioning
confidence: 68%
“…Specifically, they are involved in proline and L-DOPA degradation, cell-cell signaling and interaction, and nervous system development and function. Also, the affected genes have been implicated in psychosis including schizophrenia and bipolar disorder (Allen et al, 2008;Nyegaard et al, 2010;Lipina et al, 2013), excessive anxiety induced by stress (Bignante et al, 2008), and depressive-like behavior (Zhu et al, 2012). In addition to the association of Prodh with schizophrenia, the gene was also implicated in the neurobiology of visual processing (Magnée et al, 2011).…”
Section: Discussionmentioning
confidence: 99%